Role of maspin in cancer. Issue 1 (7th March 2013) - Berardi, Rossana; Morgese, Francesca; Onofri, Azzurra; Mazzanti, Paola; Pistelli, Mirco; Ballatore, Zelmira; Savini, Agnese; De Lisa, Mariagrazia; Caramanti, Miriam; Rinaldi, Silvia; Pagliaretta, Silvia; Santoni, Matteo; et al.
Abstract: Maspin (mammary serine protease inhibitor), is a member of the serine protease inhibitor/non‐inhibitor superfamily. Its expression is down‐regulated in breast, prostate, gastric and melanoma cancers but over‐expressed in pancreatic, gallbladder, colorectal, and thyroid cancers suggesting that maspin may play different activities in different cell types. However, maspin expression seems to be correlated with better prognosis in prostate, bladder, lung, gastric, colorectal, head and neck, thyroid and melanoma cancer. In breast and ovarian cancer maspin significance is associated with its subcellular localization: nucleus maspin expression correlates with a good prognosis, whilst in pancreatic cancer it predicts a poor prognosis. Since tumor metastasis requires the detachment and invasion of tumor cells through the basement membrane and stroma, a selectively increased adhesion by the presence of maspin may contribute to the inhibition of tumor metastasis. Furthermore the different position of maspin inside the cell or its epigenetic modifications may explain the different behavior of the expression of maspin between tumors. The expression of maspin might be useful as a prognostic and possibly predictive factor for patients with particular types of cancer and data can guide physicians in selecting therapy. Its expression in circulating tumor cells especially in breast cancer, could be also useful in clinical practice along with other factors, such as age, comorbidities, blood examinations in order to select the best therapy to be carried out. Focusing on the malignancies in which maspin showed a positive prognostic value, therapeutic approaches studied so far aimed to re‐activate a dormant tumor suppressor gene by designed transcription factors, to hit the system that inhibits the expression of maspin, to identify natural substances that can determine the activation and the expression of maspin or possible "molecules binds" to introduce maspin in cancer cell and gene therapy capable of up‐regulating the maspin in an attempt to reduce primarily the risk of metastasis. Further studies in these directions are necessary to better define the therapeutic implication of maspin.